Assesment Process of Mathematics Learning in Primary Schools in The COVID-19 Pandemic - Ajeng Rara Veronica; Wiryanto Wiryanto (EduMa: Mathematics education learning and teaching, 2021)
Mathematics learning in primary schools is transformed from conventional learning to online learning due to the COVID-19 pandemic. The learning process cannot be separated from the assessment process. This study aims to describe the process of assessing mathematics learning during the COVID-19 pandemic as well as the obstacles of the mathematics learning assessment process during the COVID-19 pandemic. This research is qualitative research using interviews and literature study methods. The results showed that the process of assessing mathematics learning in primary schools during the COVID-19 pandemic took place online in both the affective, cognitive, and psychomotor aspects. However, the process of assessing the affective, cognitive, and psychomotor aspects during the COVID-19 pandemic cannot be assessed in 100% real. This is due to the limitations of the teachers in monitoring the learning progress of students